Critical Thinking and the Construction of Scientific Literacy in the Problem-Based Learning (PBL) Model at Elementary Schools: An Integrative Literature Review - Asih Wulansari; Ratna Ekawati; Sri Rahayuningsih; Riska Pristiani; Slamet Arifin (Universitas Negeri Padang, 2026)
International assessments show that Indonesian elementary students’ scientific literacy remains low, while classroom practices still emphasize rote learning. This integrative literature review synthesizes the theoretical relationship among Problem-based Learning (PbL), critical thinking, and scientific literacy at the elementary level. Searches in Google Scholar, ERIC, and ScienceDirect identified 127 articles, of which ten peer-reviewed studies met the inclusion criteria. Content analysis revealed three main findings. First, PbL improves critical thinking and scientific literacy, with score gains of 15–25 points and N-gain values of 0.20–0.55. Second, PbL functions as the pedagogical vehicle, critical thinking as the cognitive engine, and scientific literacy as the learning outcome. Third, successful implementation depends on worksheet quality, teacher facilitation, group effectiveness, problem relevance, and time allocation. The study proposes a conceptual framework linking PbL’s five stages with Ennis’s sixteen critical-thinking indicators, providing a theoretical foundation for educators, researchers, and curriculum developers in practice